Digital Marketing as a Survival Strategy for Small Businesses in Rural Areas During Pandemics - Lulud Widjayanti (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This study examines digital marketing as a survival strategy for rural MSMEs during the pandemic, focusing on Nganjuk Regency, East Java. The background highlights the challenges of digital adaptation in rural areas, which differ significantly from urban contexts, and the high failure rates in sustaining digital operations. The research aims to understand the socio-technical adaptation processes underlying rural MSMEs' use of digital platforms by integrating the Technology Acceptance Model with Javanese cultural values. The methodology employs a 12-month mixed-methods approach, combining quantitative surveys of 70 MSMEs, digital ethnography (120 hours), transaction data analysis, and in-depth interviews. Key findings reveal four unique adaptation strategies: platform syncretism, social commerce adaptation, proxy digitalization, and offline-online bundling, demonstrating how rural MSMEs blend digital logics with local business traditions. These findings contribute to the concept of